A single indicator of noxiousness for people and ecosystems exposed to stable and radioactive substances. (June 2019) - Beaugelin-Seiller, Karine; Gilbin, Rodolphe; Reygrobellet, Sophie; Garnier-Laplace, Jacqueline
Abstract: Inspired by methods used for life cycle impact assessment (LCIA), we constructed a series of indicators to appreciate the noxiousness of radioactive materials and wastes for human and ecosystem health. According to known potential human health and ecological effects of such materials, six main impact categories were considered to initiate the development of the method: human cancer and non-cancer effects vs. ecotoxicity, considering both chemotoxicity and radiotoxicity. For ecosystems, the noxiousness indicator is based on the concept of Potentially Affected Fraction (PAF), used as a damage indicator at the ecosystem level. The PAF express the toxic pressure on the environment due to one substance. It has been enlarged to mixtures of substances as multi-substances PAF (ms-PAF), and applied to a mix of stable and radioactive substances. Combining ecotoxicity data and a simplified model of exposure of fauna and flora, we proposed a chemotoxicity indicator and a radiotoxicity indicator, ultimately aggregated into a single indicator simply by addition. According to acknowledged practices in LCIA and corresponding available data, we suggested implementing to human health an approach similar to that applied to ecosystems. We produced eigth basic indicators combining effects categories (cancer and non cancer), exposure pathways (ingestion and inhlation) and substances (chemicals and radionuclides). The principle of additivity supporting the whole proposed approach allows their complete aggregation into a single indicator also for human health. Different source terms may be then easily directly compared in terms of human and ecological noxiousness. Applied to the time evolution of a High Level radioactive Waste (HLW), the method confirmed over 1 million years the dominance of the radiotoxicity in the noxiousness of the material for both humans and environment. However there is a change with time in the ranking of the most noxious substances, with stable metals contribution going progressively up. Finally, the HLW global noxiousness, integrating human health and ecological aspects, was assessed through time at three stages and showed a temporal decrease as expected from the dominance of the radiotoxicity. Graphical abstract: Image 1 Highlights: Proposal of a unique ecological noxiousness indicator for chemicals and radionuclides. Indicator consistent with existing practices in Life Cycle Impact Assessment. Approach potentially transposable to human health. Towards a totally integrated approach of mixture noxiousness. Abstract : The ecological noxiousness of chemicals and radionuclides can be expressed by a single indicator, potentially tranposable to human health.